THE MATEMATIKA GASING METHOD AS AN INTERVENTION FOR IMPROVING ARITHMETIC FLUENCY AMONG SCHOOL STUDENTS IN AN UNDER-RESOURCED COMMUNITY CONTEXT - Waimbo, Korinus Nixon; Daullu, Melissa Aeudia; Ansanay, Yane Oktovina (Jurnal Ilmu Pendidikan Indonesia, 2026)
Difficulties with foundational arithmetic operations remain a persistent impediment to mathematical progression among primary and lower secondary school students in Indonesia, and are frequently compounded by pedagogical approaches that prioritise rote memorisation over conceptual understanding. This paper presents findings from two successive structured intervention studies examining the short-term efficacy of the Matematika GASING (Gampang, Asyik, Menyenangkan—Easy, Fun, Enjoyable) method across all four basic arithmetic operations: addition, multiplication, subtraction, and division. Study 1 (n = 24) was conducted at GGP Jemaat Ayalon Church, Argapura Resimen, Jayapura, and focused on addition and multiplication. Study 2 (n = 30) was conducted at GKPMI Jemaat Ekklesia Church, Ardipura II, Jayapura, and focused on subtraction and division. Both studies employed a one-group pre-test/post-test design. In Study 1, all five arithmetic sub-items showed positive gains, with multi-digit addition recording the highest absolute gain (+37 percentage points (pp)) and multiplication sub-items yielding a consistent +20 pp gain each. In Study 2, all seven sub-items improved, with two-digit division recording the largest relative gain (+38 pp). Across both studies and all twelve assessed sub-items, the Matematika GASING method produced consistent and educationally meaningful short-term arithmetic gains. The intervention incorporated concrete–pictorial–abstract (CPA) sequencing, mnemonic songs with movement, manipulative place-value cards, and prize-incentivised oral drills. The findings extend the GASING evidence base to non-formal community settings in Papua, and to all four basic operations within a unified research programme.